Knowing, Knowledge and Beliefs Epistemological Studies across Diverse Cultures - Khine, Myint Swe.; SpringerLink (Online service) (Dordrecht : Springer Netherlands, 2008)
Beliefs about nature of knowledge and learning, or epistemological beliefs have been an interest of educational researchers and psychologists for the past several years. New perspectives on theoretical, conceptual and methodological approaches and empirical studies on epistemological beliefs are emerging in the literature as a well-defined field of study. Studies show that personal epistemology has influence on comprehension, study strategies, learning process and academic performance. Research in this area has undergone considerable growth in the past decades and has now reached a stage of notable diversity and internationalization. Bringing together prominent educators and researchers, this book focuses on conceptual and methodical issues and state-of-the-art theoretical understanding on epistemological beliefs from educational and psychological perspectives. It is a critical and specialized source that describes recent advances in conceptualization and epistemological studies across diverse cultures.
Personal Epistemology and Culture -- Conceptual and Methodological Issues -- Assessing Teachers' Epistemological and Ontological Worldviews -- The Evolution of Self-Authorship -- Assessing the Multidimensionality of Students' Epistemic Beliefs Across Diverse Cultures -- Measurement of Epistemological Beliefs and Learning Strategies of Elementary School Children -- Empirical Studies on Cultural-specific Epistemology -- University Cultures and Epistemic Beliefs: Examining Differences Between Two Academic Environments -- Personal Epistemology in Elementary Classrooms: A Conceptual Comparison of Germany and the United States and a Guide for Future Cross-Cultural Research -- A Sociocultural Exploration of Epistemological Beliefs -- An Exploratory Study About the Role of Epistemological Beliefs and Dispositions on Learners' Thinking About an III-defined Issue in Solo and Duo Problem-solving Contexts -- Family Environment, Epistemological Beliefs, Learning Strategies, and Academic Performance: A Path Analysis -- Global Certainty Beliefs and College Major: How Strong Are Socialization Effects? -- Epistemological Beliefs, Learning, and Teaching: The Hong Kong Cultural Context -- The Use of Internet-based Instruction for the Development of Epistemological Beliefs: A Case Study in Taiwan -- Assessing the Epistemological and Pedagogical Beliefs Among Pre-service Teachers in Singapore -- Perspectives on Domain-Specific Epistemology -- Applying the Theory of an Epistemological Belief System to the Investigation of Students' and Professors' Mathematical Beliefs -- Individual Domain-Specific Epistemologies: Implications for Educational Practice -- Personal Epistemology, Understanding of Multiple Texts, and Learning Within Internet Technologies -- Epistemic Metacognition in the Context of Information Searching on the Web -- Developing Relational Epistemology Through Relational Pedagogy: New Ways of Thinking About Personal Epistemology in Teacher Education -- Knowledge and Epistemological Beliefs: An Intimate but Complicate Relationship -- Conclusion -- Challenges and Future Directions for Personal Epistemology Research in Diverse Cultures.
Keywords: PHILOSOPHY (GENERAL).; GENETIC EPISTEMOLOGY; EDUCATION -- PHILOSOPHY; CONSCIOUSNESS; APPLIED PSYCHOLOGY; PSYCHOLOGY; COGNITIVE PSYCHOLOGY; EDUCATIONAL PHILOSOPHY; CROSS CULTURAL PSYCHOLOGY; EPISTEMOLOGY